Research on the directional fracturing mechanism of multiborehole rock mass plasma blasting - Xue LI; Chuanbing WANG; Yanbing WANG; Hongjia MEI; Yanqing LI; Zhaoyang WANG; Diancai XIAO (工程科学学报)
The study examines the directional fracturing effects of plasma blasting technology when combined with slit tube and precut groove technologies. Plasma electric pulse directional fracturing tests were carried out using two groups of test variables. The aim was to explore how different slit tube shapes and precut groove spacings affect the mechanism of directional rock fracturing under various configurations of plasma blasting. In the first set of experiments, results indicated that the embedded inverted wedge-shaped slip guides crack initiation, expansion, and extension along the intended rupture surface direction compared to both positive wedge-shaped slit pipe and flat cut slit pipe. The shape of the cut slit significantly affects the directional fracturing effect during rock electrobursting. The inverted wedge-shaped slit pipe exhibits a cross-sectional area that gradually decreases from the inside to the outside, resulting in strong energy convergence during the plasma blasting process. This configuration generates maximum peak stress on both sides of the slit, ensuring a higher degree of flatness on the inner surface of the rock specimen. Consequently, it produces the fewest secondary cracks and achieves more effective directional penetration through the rock. The second group of experiments revealed that prefabricated grooved rock specimens use precut grooves to steer the direction of crack expansion and rupture surface formation. As the spacing among these grooves increases, the effectiveness of the electro-explosive fusion fracturing gradually diminishes, leading to greater deviation from the expected crack direction. When the precut slot spacing is small, the shock waves from the electro-explosive events are closer together, overlapping to form a combined shock wave. At a 40-mm slot spacing, the precut groove rock specimens exhibited optimal energy convergence from plasma electric pulses, forming a coupling surface along the precut groove line. This configuration enhances stress intensity at the rock crack tip, resulting in more precise directional cracks compared to spacing of 50 mm and 60 mm. At the same time, the directional fracturing effect of plasma blasting is more pronounced in precut groove orientations than that in slit pipe configurations, offering excellent penetration along the intended path.